G361(P) Delayed diagnosis of paediatric brain tumours – HEADSMART be brain tumour aware (www.headsmart.org.uk). (27th April 2016) - Walker, DA; Liu, JF; Merphy, L; Wilne, S
Abstract : Aims: A systematic literature review in 2005 identified that UK total diagnostic interval (TDI) ranked poorly in international comparisons. Consequently, a new NHS Evidence accredited referral guideline was developed and disseminated through a public awareness campaign to raise awareness of symptoms and the need for timely imaging. The aim of the project was to identify the tumour subtypes with the greatest proportion of delayed diagnostic intervals to inform the on-going awareness campaigns about patient groups at greatest risk of delays. Method: Total diagnostic interval (time from first symptom onset to diagnosis), patient interval (time from first symptom onset to first presentation to healthcare professionals) and healthcare interval (time from first presentation to diagnosis) data was collected by clinical champions in eighteen regional children's cancer centres. Descriptive analysis was used to compare the difference between subgroups. Results: The UK data showed a reduction in median TDI from 3.3 (2006) to 1.5 months (mean 4.9 months) by May 2013. Tumour subtypes with the skewed distribution as judged by medium and mean intervals were craniopharyngioma, low-grade glioma, germ cell tumours and optic pathway glioma with median TDIs of 3.5, 2.7, 1.3 and 2.4 months respectively (Figure 1 ). Conclusions: This strategy to accelerate brain tumour diagnosis in UK using an awareness campaign is a "world first" in paediatric cancer producing leading performance in referral intervals. Identifying the subgroups with most skewed TDIs permits this information to be used to inform future guidance and awareness campaigns.